Examining students' perception of rural practice following an educational strategy aimed at preparing postsecondary students for rural careers: a systematic review protocol for qualitative studies. Issue 9 (20th September 2022) - Button, Brenton; Regalado, Sophie M; Cameron, Erin
Abstract : Introduction: Rural areas are widely acknowledged as being at a workforce disadvantage when compared with urban populations. One of the factors contributing to this disparity is the paucity of workforce professionals who live and practice in rural areas. Educational strategies used to train these workforce professionals may help better prepare students for rural careers and thus increase retention. The purpose of this systematic review is to examine students' perceptions of rural practice following an educational strategy used to prepare students for rural careers. Methods and analysis: Searches will be conducted in the following databases: Medline (Ovid), CINAHL (Ebscohost), ERIC (Proquest), Social Services Abstracts (Proquest), PsycINFO (Proquest) and IEEE Xplore. The literature search will be limited to articles published in English in the last 20 years. Data will be extracted for author(s), year of publication (2001–2021), country of origin, research question, research design, participants, where the study takes place (eg, classroom, community), educational strategies used, theoretical approach and findings related to the research question (ie, student perceptions). Methodological validity will be assessed using standardised tools. Two independent reviewers will conduct data extraction and quality appraisal, and any disagreement will be adjudicated by discussion or with a third reviewer. Results will be presented in tabular and narrative formats. Ethics and dissemination: This review does not require formal ethical approval as it does not involve direct student contact or student-identifiable data. The final systematic review will be submitted to a peer-reviewed journal.